Structure and strain specificity for polysaccharides from king oyster mushroom (Pleurotus eryngii) fruiting bodies - Jaffali, Chahrazed; Synytsya, Andriy; Khadhri, Ayda; Aschi-Smiti, Samira; Bleha, Roman; Jozífek, Miroslav; Kvasnička, František; Klouček, Pavel (International journal of biological macromolecules, 2025)
King oyster mushroom Pleurotus eryngii is cultivated worldwide for culinary and to improve human health. However, the potential of some Mediterranean representatives of this species is still not evaluated. This work focuses on the study of polysaccharides from fruiting bodies of two Tunisian strains, P. eryngii var. elaeoselini and P. eryngii var. ferulae, and, for comparison, one deposited P. eryngii originated from Korea. Polysaccharides were successively extracted with hot water using microwave heating and 1 mol L-1 aqueous sodium hydroxide. The crude hot water extracts were purified by treating them with proteolytic enzymes, and the alkaline extracts were purified by re-dissolving with dimethyl sulphoxide. In both cases, a decrease or removal of proteins was detected. Glucans predominated in all these products; the insoluble parts also contained chitin. The purified hot water extracts contained glycogen, β-d-glucans and mannogalactan. Branching (1 → 3)(1 → 6)-β-d-glucan was the major polysaccharide in the alkali-soluble fractions, while (1 → 3)-α-d-glucan was only a minor component. The Tunisian strains demonstrated a higher proportion of water-soluble polysaccharides, compared to the alkaline soluble ones, and more β-d-glucan in the insoluble chitin-glucan complexes. Fruiting body proteins of these strains are more available for solubilisation and enzymatic or alkaline degradation and, thus, may have higher nutritional value than those of the reference strain. As a source of proteins or polysaccharides, the Tunisian endemic P. eryngii strains of this study are promising for the domestication and cultivation of fruiting bodies for gastronomic purposes in the North African region.
Keywords: Pleurotus; Polysaccharides; Fungal Polysaccharides; Species Specificity; polysacharidy; plodnice hub; King oyster mushroom; Structure; fungální polysacharidy; druhová specificita; Extraction; Fruiting Bodies, Fungal